KOMPOSISI SENYAWA ISOPRENOID PADA MANGROVE SEJATI MINOR JENIS TERUNTUN (Aegiceras corniculatum (L.) Blanco) SEBAGAI BIOMARKER DI DAERAH ESTUARINA - Julayha Julayha; Mohammad Basyuni; Lollie Agustina (Program studi Kehutanan USU, 2012)
This study described the analyzing of composition and diversity of triterpenoid and phytosterol in North Sumatera mangrove species A. corniculatum as biomarkers and input lipids in to estuarine ecosytem. Phytosterols found in the roots and leaves of A. corniculatum were stigmasterol, campesterol, β-sitosterol, and cycloartenol. Taraxerol, β-amyrin, germanicol, betulin, α-amyrin, lopenone and lupeol were the triterpenoids identified. Betulin was the major component triterpenoids had the highest content (31,8%) in the roots. This research may provide information the composition of triterpenoid and phytosterol to contribute to estimating the lipid input and as biomarker from A. corniculatum to estuarine ecosytem. Keywords : Mangrove, A.corniculatum (L) Blanco, Biomarker, Estuarine, and Lipid.